2008
DOI: 10.1073/pnas.0805953105
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of pyruvate dehydrogenase flux in the heart using hyperpolarized carbon-13 magnetic resonance

Abstract: The advent of hyperpolarized 13 C magnetic resonance (MR) has provided new potential for the real-time visualization of in vivo metabolic processes. The aim of this work was to use hyperpolarized [1-13 C]pyruvate as a metabolic tracer to assess noninvasively the flux through the mitochondrial enzyme complex pyruvate dehydrogenase (PDH) in the rat heart, by measuring the production of bicarbonate (H 13 CO 3 ؊ ), a byproduct of the PDH-catalyzed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
353
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(374 citation statements)
references
References 39 publications
19
353
2
Order By: Relevance
“…Recently, hyperpolarized 13 C pyruvate has been used to characterize cardiac metabolism noninvasively in the rat (4,5) and the pig (6). In these studies, [1][2][3][4][5][6][7][8][9][10][11][12][13] C] pyruvate was injected intravenously, and cardiac spectra were acquired with spatial localization to the heart either by coil location or by slice selection and single-step phase encoding of the field of view.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, hyperpolarized 13 C pyruvate has been used to characterize cardiac metabolism noninvasively in the rat (4,5) and the pig (6). In these studies, [1][2][3][4][5][6][7][8][9][10][11][12][13] C] pyruvate was injected intravenously, and cardiac spectra were acquired with spatial localization to the heart either by coil location or by slice selection and single-step phase encoding of the field of view.…”
Section: Introductionmentioning
confidence: 99%
“…For the global acquisitions (Protocols A and B), individual ECGgated 13 C MR pulse-acquire spectra were acquired every second for 60 s (T R , 1 s; excitation flip angle, 5°; sweep width, 13 593 Hz; acquired points, 2048; frequency centred on the C 1 pyruvate resonance), with the acquisition started immediately before the injection of the hyperpolarized pyruvate. 3 For the two-slice acquisition (Protocol C) the T R per slice was set to 0.5 s, such that data were acquired from the heart and liver in an interleaved fashion every second. All other parameters were the same as for Protocols A and B, with the exception that a slice thickness of 1 cm was used with a gap of 1 cm between slices.…”
Section: Protocol Development 221 | Experimental Overviewmentioning
confidence: 99%
“…8 In these studies, 13 C label transfer to lactate and alanine was suggested to be representative of flux through lactate dehydrogenase and alanine aminotransferase (ALT) respectively, and 13 C label flux into bicarbonate was used as a measure of flux through pyruvate dehydrogenase (PDH). Schroeder et al 3 indicated that improvements could be made to the way the data were acquired to ensure that signal from neighbouring organs was not a contaminant of data from the organ of interest. In our developed two-organ protocol, we have therefore dictated that data be selectively acquired from the organ of interest only-termed 'slice selective' henceforth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the imaging of hyperpolarized [1‐ 13 C]pyruvate and its downstream metabolic products has been used in cancer research to assess treatment response6, 7 and disease progression,8, 9 and in other tissues, such as heart10, 11 and kidney,12 to assess tissue function. The technique has now been translated to the clinic with studies in prostate cancer13 and in heart 14…”
Section: Introductionmentioning
confidence: 99%